Does the Burglar Also Disturb the Neighbor? Crime Spillovers on Individual Well-being - Christian Bünnings; Daniel Avdic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Indirect psychological effects induced by crime are likely to contribute significantly to the total costs of crime beyond the financial costs of direct victimization. Using detailed crime statistics for the whole of Germany and linking them to individual-level mental health information from the German Socio-Economic Panel, we analyze whether local crime rates affect the mental health of residents. We estimate that a one standard deviation increase in local violent crime rates significantly decreases individual mental well-being among residents by, on average, one percent. Smaller effects are found for property and total crime rates. Results are insensitive to migration and not isolated to urban areas, but are rather driven by less densely populated regions. In contrast to previous literature on vulnerability to crime, we find that men, more educated and singles react more to variation in violent crime rates in their neighborhoods. One potential explanation could be that those who are more fearful of crime have developed better coping strategies and, hence, react less to changes in crime.
Keywords: C23; I18; K42; 330